ANALISIS SELF-REGULATED LEARNING SISWA DITINJAU DARI PERBEDAAN JENIS KELAMIN - Intan Zulian Apri; Indah Sukmawati; Rezki Hariko; Lisa Putriani (IKIP Siliwangi, 2026)
The research is based on the importance of self-regulated learning (SRL) in supporting students' academic success, as they can set goals and evaluate their own learning process. However, in reality, a number of studies show that many students still have low SRL abilities. Furthermore, there are also indications of differences in SRL between males and females that need to be studied further, namely several findings that show significant differences, while other studies do not. Therefore, this study was conducted to identify differences in SRL based on gender at SMA Negeri 7 Padang. This study used a quantitative approach with a comparative method, involving 298 students as respondents, including 130 males and 168 females. The data were analyzed using descriptive statistics and inferential statistics. The findings of this study indicate that there is a significant difference between male and female students in terms of SRL, with female students scoring higher than male students (mean difference = -14.369). This shows that female students are better able to manage their own learning processes and are more responsible for their learning outcomes. These findings have important implications for guidance and counseling services in schools, especially in designing intervention strategies that are more suited to students' needs.